The Discursive Formation of Ethnic Subjectivities and Identities in Popular Romance - Moussaoui, Abdelghani (International Journal of Language and Literary Studies, 2024)
Within the framework of postcolonial studies, this paper undertakes to examine the politics of ethnic subjectivities and identities in Rebecca Stratton’s popular romance The Silken Cage. It lays bare how ‘blackness’, as an identity marker of ethnic difference, carries social and political meanings in British popular romance. This paper challenges the commonly held view of ‘skin colour’ as a mere biological feature without deeming factors and forces that have informed its conception and hence have constructed it in a number of ways. The suggested romance is worthy of study by virtue of its concern with the notion of ‘blackness’ in the colonial context. A postcolonial analysis of The Silken Cage revealed that ‘black’ subjectivity and identity are constructs that have been shaped and reshaped by historical, social, linguistic, discursive, ideological, and political dynamics. The paper also showed that Stratton’s popular narrative is an order of discourse wherein ‘blackness’ is more than a matter of pigmentation; it is a mark/mask, a uniform, a signifier, a fetish with a whole range of significance and implications. Colonialism, racial segregation, and captivity are some racist practices exploited by the writer to inscribe ethnic subjectivities and identities in the cross-cultural encounter. ‘Blackness’, in this sense, is a political, social, and ideological construct.